Enhancement the Mycosynthesis of Selenium Nanoparticles by Using Gamma Radiation - Basma H. Amin PhD (SAGE Publishing, 2021)
Selenium is a fundamental trace element of the living system. Microorganisms play a crucial role in the selenium cycle, both in the environment and in life. Biogenic selenium nanoparticles have shown promising prospects for use in medicine as an antioxidant and anticancer agent. In this study, SeNPs were biosynthesized by Penicillium citrinum . The spore suspension which was previously prepared was exposed to different doses of gamma radiation (10, 20, 30, 50, and 60 Gy). SeNPs were then produced by an irradiated P citrinum . UV spectroscopy, transmission electron microscopy, X-ray diffraction, and GSH content were assayed to evaluate the probability of P citrinum synthesizing SeNPs. In conclusion, irradiation of P citrinum by gamma ray enhances the mycosynthesis of SeNPs.